The Method of the Minimum Area of Alarm for Earthquake Magnitude Prediction - Gitis, Valeri; Derendyaev, Alexander (Frontiers in Earth Science, 2020)
An approach to the systematic forecasting of earthquake magnitudes is considered. To solve this problem, we use the method of the minimum area of alarm. Testing the approach for Kamchatka and the Aegean Region showed a satisfactory quality of the forecast of earthquakes and their magnitudes.